How alternative finance informs central themes in corporate finance - Farag, Hisham; Johan, Sofia (Journal of Corporate Finance, 2022)
This paper investigates three areas of corporate finance, and the role of alternative finance in contributing to our understanding of these areas. First, we look at disclosure, information asymmetry, and adverse selection, and how different alternative finance solutions are used to mitigate these issues. Second, we examine moral hazard and risk taking and how these behaviours are shaped by new types of alternative finance. Third, we consider the role of control rights, and show how their importance varies by context including types of alternative finance and the country-level institutional setting.